A cross-sectional study of tuberculosis among workers in Tygerberg Academic Hospital, Western Cape province, South Africa - Ayuk, Julius Nkongho (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMed)--Stellenbosch University, 2013.